Plasticity in the reproductive biology of Yellowstone cutthroat trout Oncorhynchus virginalis bouvieri in Yellowstone Lake following lake trout Salvelinus namaycush invasion - Michelle A. Briggs; Molly A. H. Webb; Christopher S. Guy; Todd M. Koel (Journal of Fish Biology, 2026)
Yellowstone cutthroat trout Oncorhynchus virginalis bouvieri in Yellowstone Lake are the focus of intensive conservation efforts due to the threat of predation by invasive lake trout Salvelinus namaycush . Suppression gillnetting has reduced the abundance of predatory lake trout, and the Yellowstone cutthroat trout population is recovering. Long‐term monitoring indicates the size structure of the population shifted following lake trout invasion, suggesting that reproductive demographic rates of Yellowstone cutthroat trout may have changed. Length at 50% probability of maturity, as assessed using histological analysis of gonadal tissue, was 479 mm (95% confidence interval [CI] 467–490 mm) for females and 406 mm (95% CI 386–430 mm) for males, compared to 330 mm for males and females historically. Currently, age at 50% probability of maturity is 6.6 for females and 5.4 for males. The rate of skipped spawning was 3% for females and 38% for males. Mean absolute fecundity was 2897 ovarian follicles/individual at present compared to 1141 ovarian follicles/individual before lake trout invasion. Mean relative fecundity was 2157 ovarian follicles/kg. This research illustrates the plasticity in the reproductive strategies of fishes as a result of an invasive species. Understanding the reproductive biology of fish populations is vital for effective fisheries management, and these results are integral to a population model that can be used to develop new conservation benchmarks for Yellowstone cutthroat trout.